A game theoretic model of multinational firm location - Pontes, José Pedro (2021)
The paper deals with a location game involving two symmetric firms. The players choose strategies in a spatial setting made up by two asymmetric countries, where the smallest country has a labour cost advantage. Determination of equilibrium location patterns enables to assess under what conditions both forms of foreign direct investment (horizontal and vertical) will take place in terms of a set of parameters (namely market size, relative size of the small country, and extent of its cost advantage). The firms interact through input transactions that bring about multiplicity of equilibria. An application to the evolution of the Portuguese car industry is performed.